Anatomical characterization of 18 commercially important varieties of Phoenix dactylifera L. by using microscopy. Issue 12 (12th July 2021) - Hussain, Amir; Zafar, Muhammad; Mahmood, Tariq; Khan, Amir Muhammad; Arfan, Muhammad; Ozdemir, Fethi Ahmet; Ahmad, Mushtaq; Yaseen, Ghulam; Fatima, Anam; Sultana, Shazia; Asif, Amna
Abstract: Date palm ( Phoenix dactylifera L.) is an important traditional crop having socioeconomic values. To best of literature review and our knowledge, there is a gap of taxonomic study on the role of morpho‐anatomical features of date palm for correct identification of its varieties. With the advancement in the field of microscopy, anatomical features are considered very effective taxonomical markers. The present study was aimed to analyze the taxonomic variations using leaf epidermal anatomy and to highlight the importance of leaf epidermis to resolve identification ambiguities among the different varieties of date palms. The study includes analysis of leaf epidermal anatomy of 18 different commercial varieties of date palm collected from different areas of Pakistan. A diverse range of shape and size of epidermal cells, subsidiary cells, guard cells, stomata, stomatal pore was observed on abaxial as well as adaxial among studied date palm varieties via LM and found to be very helpful tool in discrimination of varieties. The shape of epidermal cells on both abaxial and adaxial surfaces varies including elongated, irregular, polygonal, curved, and spherical or sometime mixed of these. The values of stomatal indices on both surfaces showed wide variations. Abstract : Anatomical features have their own systematic value in discrimination of date palm varieties from each other. A diverse range of shape and size of epidermal, subsidiary and guard cells, stomata, stomatal pore was observed on both surfaces.